2020
DOI: 10.1158/1538-7445.am2020-ct146
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT146: RGX-104, a first-in-class immunotherapy targeting the liver-X receptor (LXR): Initial results from the phase 1b RGX-104 plus docetaxel combination dose escalation cohorts

Abstract: Background: RGX-104 is a small-molecule LXR agonist that modulates innate immunity via transcriptional activation of the ApoE gene. Binding of ApoE to its receptor LRP8 robustly inhibits angiogenesis and depletes myeloid derived suppressor cells (MDSC), thereby activating cytotoxic T-lymphocytes. MDSCs are associated with resistance to both checkpoint inhibitors (CPI) and chemotherapy, providing a rationale for combination therapy with RGX-104. We previously reported results of the RGX-104 monotherapy dose esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the dose-escalation portion of the trial, neutropenia was reported as a DLT, but the number of affected patients was not included. Details regarding other AEs were not disclosed, however, the authors mentioned these were consistent with the individual toxicity profiles of docetaxel and RGX-104 [ 51 ]. It appears response rates did improve with combination therapy.…”
Section: Stimulatory Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations
“…In the dose-escalation portion of the trial, neutropenia was reported as a DLT, but the number of affected patients was not included. Details regarding other AEs were not disclosed, however, the authors mentioned these were consistent with the individual toxicity profiles of docetaxel and RGX-104 [ 51 ]. It appears response rates did improve with combination therapy.…”
Section: Stimulatory Pathwaysmentioning
confidence: 99%
“…RGX-104 is an oral molecule that targets and stimulates LXR-β on the surface of immune cells. This promotes the transcription of apolipoprotein E which leads to MDSC inactivation, activation of cytotoxic T cells, and systemic pro-inflammatory and anti-tumor immune response [ 51 ]. RGX-104 is being studied as monotherapy or in combination with docetaxel in a phase I clinical trial in patients with advanced solid or hematologic malignancies (NCT02922764).…”
Section: Stimulatory Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the LXR agonists exhibit significant synergistic effects in combination with the chemotherapy drugs there is a high need for more combination studies. In 2020, a phase 1b study of RGX-104 and docetaxel combination showed their safety and pharmacodynamic profiles in checkpoint inhibitors refractory patients ( Lim et al, 2020 ).…”
Section: Lxrs Ligandsmentioning
confidence: 99%